High-priority battlefield items and television sets: How sanctions reduced Russians' access to goods - Iikka Korhonen; Heli Simola (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2024)
We examine Russian imports since a coalition of countries imposed sanctions on exports to Russia. As Russia no longer publishes detailed statistics on foreign trade, we rely on export data from its largest trading partners (mirror statistics). We are particularly interested in trade diversion, i.e. the extent to which Russian imports have shifted from sanctioning countries to other countries. Our analysis is based on monthly export data and focuses on technology goods (HS codes 84 and 85) utilizing a difference-in-difference approach. Our dataset covers exports to Russia at the HS6-level of disaggregation from 26 sanctioning and 14 non-sanctioning countries during 2018-2023. We find that the exports of sanctioning countries to Russia fell drastically overall, with exports of sanctioned goods declining more than average exports. On the other hand, the export of sanctioned goods to Russia by non-sanctioning countries have risen more than their overall exports, indicating that Russia has managed to replace some goods no longer available from sanctioning countries, but not all of them.
urn:nbn:fi-fe202402278890
Keywords: F12; F14; F51; 330; Russia; sanctions; foreign trade